: Program “CAHAYA TBC” (Curahan Hati Yang Sakit TBC) - Rohana, I Gusti Ayu Putu Desy; Saprianto, Saprianto; Hasan Martadinata, Umar; Zanzibar, Zanzibar (LPPM Univ. Ibn Khaldun Bogor, 2023)
Tuberculosis (TB) is an infectious disease that causes the second death after the Human Immunodificiency Virus. Compliance with TB treatment is very important to achieve the Millennium Development Goals (MDGs) in the context of eliminating TB. Health problems in OKU Regency note that TB is the 10th type of infectious disease with the highest incidence rate. The partner's problem from the results of the preliminary study is that the provision of TB treatment services, strengthening the motivation of Drug Swallowing Supervisors (PMO), and providing information/education is not yet optimal. The solution implemented by the service team is the implementation of the